A Novel Method for Voltage Sag Source Location Based on HHT and GA-BP - Zhen YANG; Yuchao MA; Li LI; Xin LI; Ziying MA (Zhongguo dianli)
Aiming at the low accuracy of traditional voltage sag source positioning methods, this paper proposes a new location method based on HHT and GA-BP. Firstly, the EEMD(ensemble empirical mode decomposition) Hilbert-Huang Transform (HHT) is used to process the voltage and current during the fault period, and the effective eigenvalues - the current real part Icosθ and system trajectory slope k are obtained. Then the GA-BP neural network is used to classify the effective eigenvalues to get the initial location of the voltage sag source. And then, the moth to flame optimization (MFO) algorithm is used to solve the mathematical model of voltage and current of the fault line, so that the precise location of the voltage sag source is obtained. At the same time, the fault types are distinguished according to the relationship between the three-phase voltage amplitudes. Finally, a simulation model of a dual power supply system is used to verify the proposed method, and the simulation results show that the proposed method has high accuracy and precision in positioning and can precisely locate the voltage sag source.